أداة التقييم الأصيلي لمهارة الكلام من خلال مشروع فيديو حواري الصف التاسع: Authentic Assessment Tool For Speaking Skills Through A Ninth Grade Video Dialogue Project - Ali Andra Prasetyo; Umi Baroroh (Journal of Arabic Language Teaching, 2025)
This study aims to evaluate the quality of speaking assessments in the ninth-grade Arabic textbook for Madrasah Tsanawiyah (MTs) and reconstruct it into an authentic assessment instrument using a conversation video project approach. The research addresses a critical gap in the current textbook, which predominantly relies on rote memorization tasks and lacks systematic scoring rubrics, leading to subjective evaluation. The study employs a qualitative method with a content analysis approach. Data were collected from primary sources (the 9th-grade textbook) and secondary sources (Sukenti's authentic assessment theory). The analysis procedure involved diagnosing existing assessment items, benchmarking them against authentic standards, and reconstructing a new assessment model. The results reveal that the textbook lacks objective indicators and focuses on lower-order thinking skills. Consequently, this study reconstructs the assessment system by developing an integrative instrument comprising five authentic components: project tasks, performance rubrics, observation sheets, self-assessment, and portfolios. Subject matter experts theoretically validated this reconstructed model, serving as a methodological solution to enhance communicative competence assessment, reduce speaking anxiety, and align with the principles of the "Merdeka Curriculum" and "Profil Pelajar Pancasila."